New synonyms and redescription of two little-known Thiodia species (Lepidoptera, Tortricidae): T. ursulana (Kennel, 1919) comb. nov. and T. klapperichi (Razowski, 1967) comb. nov. - Bidzilya, Oleksiy; Blackstein, Hans; Budashkin, Yuriy; Šumpich, Jan; Tsvetkov, Eugene (Zootaxa, 2022)
The lectotype of Semasia ursulana Kennel, 1919 is designated. The name of the species is recombined as Thiodia ursulana (Kennel, 1919) comb. nov. and considered as a senior synonym of Thiodia aequilibris Tsvetkov, 2017 syn. nov. The female genitalia of this species are described for the first time. Eucosma buratana Blackstein, 2014 syn. nov. described from Tajikistan is synonymised with Thiodia klapperichi (Razowski, 1967) comb. nov. The latter species was known from the male holotype from Afghanistan. We report T. klapperichi from Turkmenistan for the first time and describe hitherto unknown female of this species. Adults and male genitalia of the type specimens of T. ursulana and T. klapperichi are illustrated. Thiodia glandulosana Walsingham, 1907 is transferred to Epinotia Hübner [1825]: Epinotia glandulosana (Walsingham, 1907) comb. nov. An annotated checklist of 27 species of Thiodia is given. In addition, the holotypes of Thiodia dahurica (Falkovitsh, 1965), Thiodia densistriata (Falkovitsh, 1964) and Thiodia hyrcana Kuznetzov, 1976 are illustrated for the first time